Some selected concepts on man in psychology and their impact on education - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah; Mustapha, Maziah (2018)
Man who occupies the highest pedestal in the hierarchy of God’s creations has derailed himself from the lofty ideas and idealism mentioned in the Holy Scriptures. As a result of this, war, terrorism, racism, environmental degradation, corporate capitalism, etc. are all happening at an enormous rate. War that should have ended after the Second World War is still going on either in small or large scale in many parts of the world. Education that used to instill values and all the humanly qualities in man in the past is somehow at the moment failing due to globalization and commodification of education. In light of the new reality of the world today, this philosophical paper intends to investigate the concepts on man showcased to the world by psychoanalysis, behaviorism, humanistic and Islamic psychologies. Upon identifying the various concepts on man, this research will perform a contrastive analysis on the impact of such theories when applied in the field of education. Very precisely, on the type of man they can produce at the end of one’s educational endeavor. The researchers will collect the relevant data through the library research method and analyze them by using the comparative and textual analysis methods which fall under the qualitative paradigm.